Key stages of the global information space: from first news agency to the internet - V V Sbruev (RUDN Journal of Studies in Literature and Journalism, 2011)
The article was prepared on the basis of the report History and Journalism: development of information society which was delivered by the author of this article in the course of the International Summer School-Seminar Journalism and Science: preparation and implementation of research and education program for scholars and journalists held at Peoples' Friendship University of Russia on July 4 - July 8, 2011.